If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -8)(x + 3) = 1 + -5x Reorder the terms: (-8 + x)(x + 3) = 1 + -5x Reorder the terms: (-8 + x)(3 + x) = 1 + -5x Multiply (-8 + x) * (3 + x) (-8(3 + x) + x(3 + x)) = 1 + -5x ((3 * -8 + x * -8) + x(3 + x)) = 1 + -5x ((-24 + -8x) + x(3 + x)) = 1 + -5x (-24 + -8x + (3 * x + x * x)) = 1 + -5x (-24 + -8x + (3x + x2)) = 1 + -5x Combine like terms: -8x + 3x = -5x (-24 + -5x + x2) = 1 + -5x Add '5x' to each side of the equation. -24 + -5x + 5x + x2 = 1 + -5x + 5x Combine like terms: -5x + 5x = 0 -24 + 0 + x2 = 1 + -5x + 5x -24 + x2 = 1 + -5x + 5x Combine like terms: -5x + 5x = 0 -24 + x2 = 1 + 0 -24 + x2 = 1 Solving -24 + x2 = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + x2 = 1 + 24 Combine like terms: -24 + 24 = 0 0 + x2 = 1 + 24 x2 = 1 + 24 Combine like terms: 1 + 24 = 25 x2 = 25 Simplifying x2 = 25 Take the square root of each side: x = {-5, 5}
| 20+t=66 | | 18x^3-63x^2+9x= | | 0=2x^2+22x+48 | | 1/9+1/9+1/9 | | x-5=2y-5 | | 1/3(6x-9)-10 | | 2+(x-4)+8=3x-8 | | 3x+35=5x-15 | | 2x^2-24x+70=0 | | (6n+3)(6n-4)=0 | | 1/(x-2)-1/(x^2-4) | | 3x(x+7)(3x-4)=0 | | a+d+d+a=24 | | 3x-14+x=90 | | 6-2(x+3)=4x-3 | | 9n-6=57 | | 6x-25+7x+49=180 | | x+1/4x-18=0 | | 9=2b-b-10 | | 128n-3=95 | | 5T+7=4t-7 | | 16x+4=17x | | 2.5=12.5 | | 17-16=x/-8 | | (-12x-5)-(6x-8)= | | 6/2=4/x | | 5+4y=2y | | 1/3d=4/9 | | -12z=10 | | w-8=14 | | (4r-2)(5r+2)= | | x=3y-18 |